Boerhaave Syndrome in a Paediatric Patient With Diabetic Ketoacidosis: A Case Report - Alkhalifah, Yasir S (Scripta Medica, 2024)
Diabetic ketoacidosis is a serious and potentially life-threatening complication of type 1 diabetes mellitus (T1DM), which often results from poor glycaemic control. While diabetic ketoacidosis is well documented, rare complications such as Boerhaave syndrome can considerably increase morbidity. This case report presents a 14-year-old girl with poorly controlled T1DM and celiac disease who was admitted with diabetic ketoacidosis and developed severe vomiting and abdominal pain. Imaging studies revealed the presence of pneumomediastinum, which raised concerns about oesophageal injury and a diagnosis of Boerhaave syndrome was made. The patient was managed conservatively with correction of metabolic acidosis, intravenous antibiotics, supportive care and close monitoring. Her condition improved gradually, with resolution of ketoacidosis and stabilisation of the pneumomediastinum without invasive intervention. This case highlights the importance of early identification and the adoption of a multidisciplinary approach in managing atypical complications of diabetic ketoacidosis. Timely intervention can ensure favourable outcomes even in the presence of severe complications.